Anxiety and Depression in Patients Hospitalized With Chronic Kidney Disease in Barranquilla Clinics, Colombia (2018)
The purpose of this study is to determine the levels of anxiety and depression in patients aged between 18 and 70 years, hospitalized with chronic kidney disease in a clinic entity of the city of Barranquilla. The type of research is descriptive, presenting the information through the indicators and statistical tables, the Hospital Scale of Anxiety and Depression of, Zigmond & Smith (1983), which evaluates the detection of depressive and anxious disorders in the non-psychiatric hospital context. The application of the Scale was performed in the hospital entity of the city of Barranquilla to 50 patients with Chronic Kidney Disease. The results they are beneficial in the short term, because they create new research proposals applied to another population group diagnosed with chronic diseases, especially for the evaluation and intervention in the area of health psychology. In the long term, new theories, methods of intervention and evaluation applied to the population of patients with chronic kidney disease will be studied. In the same way, the results show marked trends related to depression, an aspect that is consistent with the deterioration that affects the individual in the course of the disease and also show a positive correlation of the study variables, depression and anxiety disorders in patients with CKD can be due to a symptomatology or consequence of psychological burnout.